2008
DOI: 10.1159/000175837
|View full text |Cite
|
Sign up to set email alerts
|

Turkey Coronavirus Non-Structure Protein NSP15 – An Endoribonuclease

Abstract: Turkey coronavirus (TCoV) polyprotein was predicted to be cleaved into 15 non-structural proteins (nsp2 to nsp16), but none of these nsps have been characterized. TCoV nsp15 consists of 338 residues and shares 40% sequence similarity to U-specific Nidovirales endoribonuclease (NendoU) of severe acute respiratory syndrome coronavirus. Objective: The purpose of the present study was to characterize TCoV nsp15. Methods: The TCoV nsp15 gene was cloned into pTriEX1 and expressed as a C-terminal His-tagged recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…As a result, intermediate precursors likely exist and interactions with other viral nsps may interfere with its self-interaction. In this regard, it is important to note that although bacteria-expressed nsp15 forms hexamers and exhibits endonuclease activity in vitro (Cao et al, 2008;Guarino et al, 2005), these biochemical properties have yet to be demonstrated in virus-infected or ectopically expressed cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, intermediate precursors likely exist and interactions with other viral nsps may interfere with its self-interaction. In this regard, it is important to note that although bacteria-expressed nsp15 forms hexamers and exhibits endonuclease activity in vitro (Cao et al, 2008;Guarino et al, 2005), these biochemical properties have yet to be demonstrated in virus-infected or ectopically expressed cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, comparative sequence analysis has predicted that coronaviral nsp15 may have endoribonuclease activity similar to Xenopus endoU (XendoU) that cleaves U on single-stranded RNA molecule and requires Mn 2+ as a cofactor (Bhardwaj et al, 2004;Gioia et al, 2005;Laneve et al, 2003). The nidoviral endoU (NendoU) activity was first demonstrated biochemically in vitro for SARS-CoV nsp15 expressed from bacteria (Bhardwaj et al, 2004), and subsequently confirmed in bacteria-expressed nsp15s from MHV (Kang et al, 2007;Xu et al, 2006), human CoV-229E (Ivanov et al, 2004), turkey CoV (Cao et al, 2008), and in nsp11 of equine arteritis virus, a cousin of coronavirus within the order of Nidovirales (Nedialkova et al, 2009). Unlike XendoU which acts as a monomer, NendoU appears to maintain its activity as a hexamer in vitro (Guarino et al, 2005;Joseph et al, 2007;Ricagno et al, 2006;Xu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide bonds are rare in proteins that function in the cytosol, but for instance in coronavirus nonstructural proteins, several cases have been observed. [42][43][44] We presume that the side chain of Cys111 can adopt a different conformation and form a disulfide bond with Cys115, perhaps after substrate binding to facilitate the proteolysis. This should be addressed in the future with a substrate-enzyme complex structure.…”
Section: Discussionmentioning
confidence: 99%
“…42 Endoribonuclease activity has been confirmed for nsp15 from the coronaviruses SARS-CoV, HCoV-229E, MHV-A59, Avian infectious bronchitis virus (IBV) and Turkey coronavirus and for nsp11 from the arteriviruses Equine arteritis virus (EAV) and PRRSV. 41,42,[75][76][77] Similar to XendoU, NendoUs are endoribonucleases that cleave 3' of pyrimidines, preferring uridine over cytidine and releasing products with 2',3'-cyclic phosphate and 5'-OH ends. A marked preference for cleavage after unpaired over paired pyrimidines has been demonstrated comparing the efficiency of cleavage of ssRNA versus dsRNA and using an RNA with a known secondary structure.…”
Section: The Nidovirus Endoribonuclease Specific For Uridylate Nendoumentioning
confidence: 99%